2021
DOI: 10.3390/jcm10020310
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Carriage of Carbapenemase-Producing Enterobacteriaceae: Clinical Risk Factors and the Influence of Carbapenemase and Organism Types

Abstract: Prolonged carriage of carbapenemase-producing Enterobacteriaceae (CPE) constitutes a substantial epidemiologic threat. This study aimed to evaluate whether the types of carbapenemase and organism can affect the duration of carriage and to evaluate the clinical factors associated with prolonged carriage. We retrospectively reviewed data for patients admitted between May 2013 and August 2018 who were identified as CPE carriers. A total of 702 patients were identified; the major types of carbapenemase and organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
2
6
1
Order By: Relevance
“…Previous exposure to fluoroquinolones and carbapenems is independent risk factors for CRE infection 5,24 . We found that prior exposure to carbapenems was an independent risk factor for clinical CRE infection in rectal CRE carriers, which is consistent with previous study 22 . However, prior exposure to fluoroquinolones was not associated with CRE subsequent infection among rectal CRE carriers in this study.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Previous exposure to fluoroquinolones and carbapenems is independent risk factors for CRE infection 5,24 . We found that prior exposure to carbapenems was an independent risk factor for clinical CRE infection in rectal CRE carriers, which is consistent with previous study 22 . However, prior exposure to fluoroquinolones was not associated with CRE subsequent infection among rectal CRE carriers in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies, the main carbapenem‐resistant bacteria in bloodstream infections among rectal carriers was K. pneumoniae (73.8% of the cases) 21 . A recent study on 702 patients suggested that carriers of carbapenemase‐producing K. pneumoniae may have an increased likelihood of prolonged carriage 22 …”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations